EPIDERMOID INCLUSION CYST OF THE PERINEUMA RARE CASE REPORT IN A 50 YEARS OLD MALE - Ali, Syed Asad; Tahir, S M; Memon, Abdul Sattar; Dahri, Adeel Abbas (Journal of Ayub Medical College Abbottabad, 2009)
A 50 year old male presented with a history of mid line painless swelling in the perineum for last 4 years. The patient’s only concern was a perineal swelling which was gradually increasing in size. Clinical examination mimics subcutaneous lipoma with soft lobulated surface with positive slip sign. The base line investigations were within normal limits. Complete surgical excision of the cyst performed. Histopathology confirmed epidermal inclusion cyst with no evidence of malignancy. Patient discharged on next day. The follow-up visits were un-remarkable. Perineal epidermal inclusion cyst is a rare entity and only few cases have been reported. Keywords: Epidermal Inclusion Cyst, Perineum, Surgical Excision